Application of grounded metallic enclosing mesh for expanding rated voltage of dry‐type transformer. Issue 5 (1st May 2016) - de Oliveira, Luiz F.; Cabral, Sérgio H.L.
Abstract : Thanks to the awareness of safety, dry‐type transformer has experienced a significant demand, lately. However, a limiting condition for an even more significant increase in its demand is that its maximum rated voltage is about 36 kV, in most of countries. Beyond this limit, dry‐type transformer becomes definitely uneconomical in comparison to oil‐filled transformer because of the expressive increase in dielectric clearance distances and consequent drawbacks. Thus, the aim of this work is to propose a way for overcoming this limit, based on shielding the electric field of the high‐voltage windings of the dry transformer with a grounded metallic mesh. The effectiveness of the proposition is shown whereas most of the undesirable of its consequences are also evaluated. Namely, losses and temperature rise concerns as well as items of standard dielectric tests, which are analysed through computer modelling and simulation. Due to its outstanding importance, analysis of distribution of lightning impulse voltage along the high‐voltage winding is also experimentally performed. The result is a set of key hints given by the authors and to be observed by transformer designers for making real the production of dry‐type transformer with a rated voltage higher than 36 kV.